CT of the Heart Principles and Applications - Schoepf, U. Joseph; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
The introduction of fast ECG-synchronized computed tomography (CT) techniques enables imaging of the heart with a combination of speed and spatial resolution unparalleled by other noninvasive imaging modalities. Applying these modalities for the evaluation of coronary artery disease is a topic of active current research. Coronary artery calcium measurements are investigated as a marker for cardiac risk stratification. With contrast-enhanced CT coronary angiography, coronary arteries can be visualized with unprecedented detail, so that noninvasive stenosis assessment appears within reach. With increasing accuracy CT enables evaluation of coronary artery bypass grafts and stents. The cross-sectional nature of CT may to some degree allow noninvasive assessment of the coronary artery wall. CT for evaluating cardiac perfusion, motion, and viability is being investigated. In CT of the Heart, leading radiologists, cardiologists, physicists, engineers, and basic and clinical scientists from around the world survey the full scope of current developments, research, and scientific controversy regarding principles and applications of cardiac CT. Richly illustrated with numerous black-and-white and color images, the book discusses the interpretation of CT of the heart in a variety of clinical, physiologic, and pathologic applications. The authors emphasize current state-of-the-art uses of computed tomography, but also examine emerging developments at the horizon. They review the technical basis of CT image acquisition as well as the tools for image visualization and analysis. Meticulous and comprehensive, CT of the Heart authoritatively defines the current status of computed tomography of the heart, offering a truly balanced view of its technology, applications, significance, and future potential.
and Historical Background -- CT of the Heart -- Technical Background -- Electron Beam CT of the Heart -- Scan Techniques for Cardiac and Coronary Artery Imaging With Multislice CT -- Image Reconstruction for ECG-Triggered and ECG-Gated Multislice CT -- Phase-Correlated Image Reconstruction Without ECG -- Radiation Dose From CT of the Heart -- Detection and Quantification of Coronary Calcium -- Coronary Calcium Screening -- Coronary Calcium Scanning -- Detection and Quantification of Coronary Calcium With Electron Beam CT -- Detection and Quantification of Coronary Calcium With Dual-Slice CT -- Detection and Quantification of Calcified Coronary Plaque With Multidetector-Row CT -- Coronary Calcium Scoring With Multidetector-Row CT -- Noninvasive Quantification of Coronary Calcium -- Contrast-Enhanced CT of the Heart -- CT of the Pericardium -- Multidetector-Row CT for Assessment of Cardiac Valves -- Multislice CT of the Heart and Great Vessels in Congenital Heart Disease Patients -- Imaging of Cardiac and Paracardiac Masses and Pseudotumors -- Multidetector-Row CT Assessment of Left-Ventricular Function -- Imaging Intramyocardial Microcirculatory Function Using Fast Computed Tomography -- Approaches for Assessing Myocardial Viability With Multidetector-Row CT -- Contrast-Enhanced CT of the Heart -- Anatomy of the Coronary Arteries and Veins in CT Imaging -- Techniques and Protocols for Acquisition and Display of Contrast-Enhanced CT Angiography -- Contrast Material Injection Techniques for CT Angiography of the Coronary Arteries -- Visualization Techniques for Contrast-Enhanced CT Angiography of Coronary Arteries -- CT Angiography for Assessment of Coronary Artery Anomalies -- Multidetector-Row CT for Assessment of Kawasaki Disease -- Multidetector-Row CT of the Coronary Arteries for Planning of Minimally Invasive Bypass Surgery -- CT Angiography for Assessment of Coronary Bypass Grafts -- Contrast-Enhanced Electron Beam CT and Multidetector-Row CT in the Evaluation of Coronary Stent Patency -- CT Angiography for the Detection of Coronary Artery Stenosis -- Complementary Use of Coronary Calcium Scoring and CT Angiography -- CT vs Magnetic Resonance for Imaging of the Coronary Arteries -- Contrast-Enhanced CT of the Heart -- Pathology and Pathophysiology of Coronary Atherosclerotic Plaques -- Pathogenesis of the Vulnerable Atherosclerotic Plaque -- Multidetector-Row CT Imaging of Clinical and Preclinical Coronary Atherosclerosis -- Multidetector-Row CT vs Intravascular Ultrasound for Coronary Plaque Characterization -- Multidetector-Row CT vs Magnetic Resonance Imaging for Coronary Plaque Characterization -- Multidetector-Row CT for Detection of Noncalcified and Calcified Coronary Lesions.
Keywords: Medicine; Radiology; Medicine & Public Health; Imaging / Radiology; Electronic books